Critical Thinking for Writing Using Facebook Under COVID-19 Lockdown: A Course Model for English Literature Students - Almansour, Elaf; Kurt, Mustafa (Frontiers in Psychology, 2022)
Abstract The aim of this paper is to explore the effectiveness of critical thinking for improving the writing skill of undergraduate Arab students who study English Literature at Saudi universities under lockdown circumstances due to the Covid-19 pandemic. At the same time, it explores the impact of implementing Facebook as an online Constructivist tool to improve this skill. A general overview of the status of English language education in Saudi Arabia is briefly presented to shed light on the ongoing English language challenges in learning writing for undergraduate students in the English language and literature departments, which got more manifested due to the current status of education mode with the emergence of the pandemic. Two-group posttest-only randomized experiment was employed to evaluate the effectiveness of the proposed model, using the infusion and constructivism approaches. A total of 40 students enrolled in a literature course at a private university in Saudi Arabia participated in the experiment. The treatment was conducted through utilizing Facebook. The results demonstrated that students’ improvement in English writing was due to the combination of the infusion of a set of critical skills and the constructivist teaching and learning mode.